INNOVATIVE METHODS OF QUALITY CONTROL OF FOOD INDUSTRY PRODUCTS IN THE CONTEXT OF PUBLIC ADMINISTRATION - SEMBAY, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The author of the article defines the methods of quality control of products of the food industry of Ukraine in modern conditions, emphasises the need to apply management technologies to the analysis of public administration processes and introduction of innovations into practice. The author examines the components of product quality control methods in the context of priority innovation areas of the food industry and ensuring food safety and public health protection. The author analyses innovative methods of quality control in the food industry in accordance with effective public administration strategies. The author emphasises the need for a systematic approach to managing strategic transformations in the food industry, due to the active use of innovative methods of product quality control. Based on the analysis of the above material, the views and opinions of experts, we note that the methods of controlling the quality of food products in the current realities of Ukraine are not only of primary importance, but also of strategic importance, because our country must follow the path of creating a system built on the basis of one defining organizational structure, as it is spread in the EU countries, which will ensure control over the quality and safety of food products. The defining role of public management through the use of various powers of the executive power and the implementation of management functions in order to implement the functions of state policy in the food industry is evident in the activities of this structure. At the same time, in this context, civil society and specialized professional public associations acquire a decisive importance. Among the identified innovative methods of quality control of food industry products in Ukraine, the use of sensor technologies and the Internet of Things (IoT), methods of genetic analysis, the use of blockchain, biosensors and nanotechnologies, electronic tongues and noses, and automatic control systems (SCADA) can be singled out. which collectively are able to provide a qualitative leap to new conditions of production and quality control of food products. A more detailed analysis of the theoretical and practical aspects of fundamentally new technologies and methods of food product quality control, which would have a health-improving effect on the human body, ensure the elimination of the deficiency of necessary elements and weaken the negative effects of the external environment, can be considered as the perspectives of research in this context.